Experimental investigation of control of NOx emissions in biodiesel-fueled compression ignition engine - Agarwal, Deepak; Sinha, Shailendra; Agarwal, Avinash Kumar (Renewable energy, 2006)
Experimental investigation of control of NOx emissions in biodiesel-fueled compression ignition engine is presented. Biodiesel is an alternative fuel consisting of the alkyl esters of fatty acids from vegetable oils or animal fats. Vegetable oils are produced from numerous oil speed crops. Research has shown that biodiesel-fueled engines produce less carbon monoxide (CO), unburned hydrocarbon (HC), and particulate emissions compared to mineral diesel fuel but higher NOx emissions. Exhaust gas recirculation (EGR) is effective to reduce NOx from diesel engines because it lowers the flame temperature and the oxygen concentration in the combustion chamber. However, EGR results in higher particulate matter (PM) emissions. Application of EGR with biodiesel blends results in reductions in NOx emissions without any significant penalty in PM emissions of brake specific energy consumption (BSEC).